Rede urbana e redes de serviços bancários, postais e educacionais do Rio Grande do Norte: coexistências de hierarquias - Edseisy Silva Barbalho Tavares (Confins)
The urban network of Rio Grande do Norte in the current period displays a configuration resulting from the characteristics of the technical-scientific-informational period in which emerges a superposition of networks that cohabit in that territory. This urban network structure manifests itself as a result of the changes promoted in the territory, of which the expansion and spatialization of the new geographical fixed and financial, postal and educational spots are highlighted. In this perspective, the objective of this study is to understand the role and how the financial, postal and educational services of the different levels of education promote spatial interactions that redirect the flows in the urban network of the State, contributing to a new configuration of the urban network, as well as of the rupture of a rigid urban hierarchy. In the present work, a theoretical-conceptual and empirical research was carried out and the data collection involved banking institutions, teaching institutions and postal services, seeking to understand how these services are distributed and use the territory, and from that use, how they restructure the urban network of Rio Grande do Norte. From what could be analyzed and interpreted, it is evident that the new territory dynamics generated by these services not only guide flows towards the most hierarchical cities of the network, but it provides spatial interactions in several scales simultaneously in addition to presenting convergence of fixed and flows to not very dense centers in the context of the urban network of the State.